Outcomes of Resistance-guided Sequential Treatment of Mycoplasma genitalium Infections: A Prospective Evaluation - Read, Tim R H (Clin Infect Dis, 2019)
BACKGROUND: Rising macrolide and quinolone resistance in Mycoplasma genitalium necessitate new treatment approaches. We evaluated outcomes of sequential antimicrobial therapy for M. genitalium guided by a macrolide-resistance assay. METHODS: In mid-2016, Melbourne Sexual Health Centre switched from azithromycin to doxycycline (100 mg twice daily for 7 days) for nongonococcal urethritis, cervicitis, and proctitis. Cases were tested for M. genitalium and macrolide-resistance mutations (MRMs) by polymerase chain reaction. Directly after doxycycline, MRM-negative infections received 2.5 g azithromycin (1 g, then 500 mg daily for 3 days), and MRM-positive infections received sitafloxacin (100 mg twice daily for 7 days). Assessment of test of cure and reinfection risk occurred 14–90 days after the second antibiotic. RESULTS: Of 244 evaluable M. genitalium infections (52 women, 68 heterosexual men, 124 men who have sex with men) diagnosed from 20 June 2016 to 15 May 2017, MRMs were detected in 167 (68.4% [95% confidence interval CI, 62.2%–74.2%]). Treatment with doxycycline decreased bacterial load by a mean 2.60 log(10) (n = 56; P < .0001). Microbiologic cure occurred in 73 of 77 MRM-negative infections (94.8% [95% CI, 87.2%–98.6%]) and in 154 of 167 MRM-positive infections (92.2% [95% CI, 87.1%–95.8%]). Selection of macrolide resistance occurred in only 2 of 76 (2.6% [95% CI, .3%–9.2%]) macrolide-susceptible infections. CONCLUSIONS: In the context of high levels of antimicrobial resistance, switching from azithromycin to doxycycline for presumptive treatment of M. genitalium, followed by resistance-guided therapy, cured ≥92% of infections, with infrequent selection of macrolide resistance.